2014
DOI: 10.1111/1574-6941.12329
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic taxonomic and metabolic diversity of an intermediate salinity hypersaline habitat assessed by metagenomics

Abstract: A metagenome was obtained by pyrosequencing the total prokaryotic DNA from the water of a pond with intermediate salinity (13% salts) from a saltern located in Santa Pola, Spain. We analyzed and compared the phylogenomic and metabolic diversity of this saltern pond with respect to other two metagenomes obtained previously from the same saltern (ponds with 19% and 37% salts, respectively) and two reference metagenomes from marine and coastal lagoon habitats. A large microbial diversity, representing seven major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 72 publications
5
74
0
Order By: Relevance
“…Very recently, we have carried out metagenomic studies on three intermediate-salinity ponds (with 13,19, and 33% total salts, respectively) and a crystallizer pond (with 37% salts) by deep shotgun sequencing of environmental DNA. These studies have permitted the determination of the microbial diversity of these ponds with intermediate salinities in comparison with that of the crystallizer pond (15,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, we have carried out metagenomic studies on three intermediate-salinity ponds (with 13,19, and 33% total salts, respectively) and a crystallizer pond (with 37% salts) by deep shotgun sequencing of environmental DNA. These studies have permitted the determination of the microbial diversity of these ponds with intermediate salinities in comparison with that of the crystallizer pond (15,19).…”
mentioning
confidence: 99%
“…These studies have permitted the determination of the microbial diversity of these ponds with intermediate salinities in comparison with that of the crystallizer pond (15,19). Comparison of the 16S rRNA reads with sequences in databases indicated that the major groups at the intermediate-salinity ponds were the Euryarchaeota (which was the predominant group at the crystallizer pond), as well as the phyla Proteobacteria and Bacteroidetes.…”
mentioning
confidence: 99%
“…Full random metagenome sequencing of multiple hypersaline systems (Santa Polasaltern in Spain -13 to 37% salinity), the hypersaline lake Tyrell in Australia (29% salinity) and crystallizer ponds in the USA (18 to 38% salinity) show equally high phylotypic diversity and the general dominance of Archaea, in particular the square-shaped halophilic archaeon Haloquadratum walsbyi [38][39][40][41]. Remarkably, de novo sequence assembly of metagenomic samples from hypersaline environments has led to the discovery of a novel uncultivated class, the "Nanohaloarchaea", previously detected only once by "classic" 16S rRNA amplicon sequencing [42] but now known to be dominant in these systems across the world [39,40].…”
Section: Extremely Halophilic Habitatsmentioning
confidence: 99%
“…Detailed functional annotation of a hypersaline metagenome has shown a generally simplistic C and N biogeochemical cycling capacity, but with the capacity to use light as an energy source via various bacteriorhodopsins [41]. Haloresistance mechanisms are dominated by the capacity to synthesise compatible solutes (such as glycine, betaine, ectoine and trehalose) [41].…”
Section: Extremely Halophilic Habitatsmentioning
confidence: 99%
See 1 more Smart Citation